The “community of transition” in the dependentist sociology of Aníbal Quijano - Álvarez Ruiz, Fermín (2024)
The article addresses the problem of the community in the sociological studies of Aníbal Quijano elaborated between 1966 and 1970. These writings were produced during his stay in Chile as a researcher of CEPAL. The theoretical approach that guides these investigations is the “dependentist historical structuralism” and, in part, Marx’s historical materialism and theory of capitalism. Its object of study is urbanization and marginality in Latin American societies. The methodology chosen to investigate the problem of the community in this section of the author’s work is the “problematic approach.” The article proposes three hypotheses. The first is that in these works the community intertwines traditional and modern culture, giving rise to a sui generis configuration. The second is that from these investigations emerges a conception of the community that presents two dimensions in tension: that of emancipation and that of domination. Finally, as a conclusion, the concept of “community of transition” is resumed and it is suggested that the tension between such dimensions opens questions for future research on Quijano’s work.